Uniportal-VATS vs. open McKeown esophagectomy: Surgical and long-term oncological outcomes - Nachira, Dania; Congedo, Maria Teresa; Calabrese, Giuseppe; Tabacco, Diomira; Petracca Ciavarella, Leonardo; Meacci, Elisa; Vita, Maria Letizia; Punzo, Giovanni; Lococo, Filippo; Raveglia, Federico; Chiappetta, Marco; Porziella, Venanzio; et al. (Frontiers in Surgery, 2023)
Background:Till now there are very few reports about surgical results of Uniportal-VATS esophagectomy and no one about long-term outcomes. This study is the first comparing surgical and oncological outcomes of Uniportal-VATS with open McKeown esophagectomy, with the largest reported series and longest oncological follow-up. Methods:The prospectively collected clinical, surgical and oncological data of 75 patients, undergone McKeown esophagectomy at our Thoracic Surgery Department, from January 2012 to August 2022, were retrospectively analyzed. Nineteen patients underwent esophagectomy by thoracotomy and reconstruction according to McKeown technique while 56 by Uniportal-VATS approach. Gastric tubulization was performed totally laparoscopic or through a mini-laparatomic access and cervical anastomosis was made according to Orringer’s technique. Results:The mean operative thoracic time was similar in both accesses(102.34±15.21 min in Uniportal-VATS vs 115.56±23.12min in open, p: 0.646),with a comparable number of mediastinal nodes retrieved (Uniportal-VATS:13.40±8.12 vs open:15.00±6.86,p:0.275).No case needed conversion from VATS to open.The learning curve in Uniportal-VATS was completed after 34 cases, while the Mastery was reached after 40. Both approaches were comparable in terms of minor post-operative complications (like pneumonia, lung atelectasis, anemization, atrial fibrillation, anastomotic-leak, left vocal cord palsy, chylothorax), while the number of re-operation for major complications(bleeding or mediastinitis) was higher in open group(21.0% vs 3.6%,p:0.04). Both techniques were also effective in terms of surgical radicality and local recurrence but VATS approach allowed a significantly lower chest tube length(11.89±9.55 vs 25.82±24.37 days,p:0.003) and post-operative stay(15.63±11.69 vs 25.53±23.33,p: 0.018).The 30-day mortality for complications related to surgery was higher in open group(p:0.002). The 2-, 5- and 8-year survival of the whole series was 72%, 50% and 33%, respectively. Combined 2- and 5-year OS in Uniportal-VATS group was 76% and 47% vs 62% and 62% in open group, respectively(Log-rank,p:0.286;Breslow-Wilcoxon:p:0.036). No difference in DFS was recorded between the two approaches (5 year-DFS in Uniportal-VATS: 86% vs 72%,p:0.298) At multivariate analysis, only pathological stage independently affected OS (p:0.02), not the surgical approach p:0.276). Conclusions:Uniportal-VATS seems to be a safe, feasible and effective technique for performing McKeown esophagectomy, with equivalent surgical and long-term oncological results to standard thoracotomy, but with a faster and unharmed recovery, and a quite short learning curve.